Overview of Economic Demography: Theories and Stories from Europe. - Bautista, Cristina (Archīum Ateneo, 2019)
Economic demography studies the economic elements in the causes and consequences of population change. This chapter of the book; EU and ASEAN Regionalism: A Multidisciplinary Approach (2019); is meant to introduce students of European Studies to a basic understanding of economic demography in the context of Europe’s experience. It is not only about what happened to Europe’s population but also about how conditions in certain European countries brought thinkers to theorize relationships of economic and social variables to population. Specifically; the paper describes Europe’s population history—its patterns and trends over the past centuries—with narratives that discuss the factors that contributed to its demographic cycles. Moreover; it discusses how major economic theories on population; starting with the Malthusian view to the model of demographic transition; were formulated based on the growth and development experience of certain European nations.